(untitled) - Lennox, James G. (Cambridge, UK,New York, 2001)
In addition to being one of the world's most influential philosophers, Aristotle can also be credited with the creation of both the science of biology and the philosophy of biology. The papers collected in this volume, written by a preeminent figure in the field of Aristotle's philosophy and biology, examine Aristotle's approach to biological inquiry and explanation, his concepts of matter, form and kind, and his teleology. Gathering important essays written over a span of twenty years, this volume will be of special value to historians of science and philosophers of science
Keywords: Biology,Biology,Khoa học về sự sống,Sinh học; Philosophy,History,Triết học